Media Lokal dalam Konstelasi Komunikasi Politik di Daerah - Yusuf, Iwan Awaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2011)
The existence of the local media as a subsystem of local politics requires strong professionalism and idealism bases. Without professionalism, it was not easy for mass media to maintain their trust from society. As a business institution, the local media should elevate the quality of its management to support whole company and increase the welfare of its workers. This article will elaborates on three related topics: theoretical observation of media relations, democracy, and the process towards local democratization; responding to the regional autonomy, the role of local media in the regional authonomy on mediating political leaders and constituents; and the importance of local media role in the democratization process in Indonesia, as well as to give alternative on how a local media should be in the future, either as the democracy subsystem or as the pillar of the industry.